Novel Autoimmune IgM Antibody Attenuates Atherosclerosis in IgM Deficient Low-Fat Diet–Fed, but Not Western Diet–Fed Apoe–/– Mice. Issue 1 (January 2020) - Cherepanova, Olga A.; Srikakulapu, Prasad; Greene, Elizabeth S.; Chaklader, Malay; Haskins, Ryan M.; McCanna, Mary E.; Bandyopadhyay, Smarajit; Ban, Bhupal; Leitinger, Norbert; McNamara, Coleen A.; Owens, Gary K.
Abstract : Objective: Oxidized phospholipids (OxPL), such as the oxidized derivatives of 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine, 1-palmitoyl-2-(5-oxovaleroyl)-sn-glycero-3-phosphorylcholine, and 1-palmitoyl-2-glutaroyl-sn-glycero-3-phosphorylcholine, have been shown to be the principal biologically active components of minimally oxidized LDL (low-density lipoprotein). The role of OxPL in cardiovascular diseases is well recognized, including activation of inflammation within vascular cells. Atherosclerotic Apoe –/– mice fed a high-fat diet develop antibodies to OxPL, and hybridoma B-cell lines producing natural anti-OxPL autoantibodies have been successfully generated and characterized. However, as yet, no studies have been reported demonstrating that treatment with OxPL neutralizing antibodies can be used to prevent or reverse advanced atherosclerosis. Approach and Results: Here, using a screening against 1-palmitoyl-2-(5-oxovaleroyl)-sn-glycero-3-phosphorylcholine/1-palmitoyl-2-glutaroyl-sn-glycero-3-phosphorylcholine, we generated a novel IgM autoantibody, 10C12, from the spleens of Apoe –/– mice fed a long-term Western diet, that demonstrated potent OxPL neutralizing activity in vitro and the ability to inhibit macrophage accumulation within arteries of Apoe –/– mice fed a Western diet for 4 weeks. Of interest, 10C12 failed to inhibit atherosclerosis progression in Apoe –/– mice treated between 18 and 26 weeks of Western diet feeding likely due at least in part to high levels of endogenous anti-OxPL antibodies. However, 10C12 treatment caused a 40% decrease in lipid accumulation within aortas of secreted IgM deficient, sIgM –/– Apoe –/–, mice fed a low-fat diet, when the antibody was administrated between 32-40 weeks of age. Conclusions: Taken together, these results provide direct evidence showing that treatment with a single autoimmune anti-OxPL IgM antibody during advanced disease stages can have an atheroprotective outcome. Abstract : Supplemental Digital Content is available in the text.